The Urgency Of Religious Forum As The Basis Of Education For Corruption Prevention Among Government Officials (A Multi-Site Study In Malang Raya Government Mosques) - Ahmad Barizi; Siti Rohmah; Moh. Anas Kholish (Didaktika Religia, 2021)
This study aims to see the construction of the preachers and preachers about the urgency of preventing corruption through the religious forum in the mosque of the Government of Malang Raya. In addition, this study also aims to analyze and analyze the role of the religious pulpit in the Malang Government mosque in preventing corruption. The approach used in this research is a qualitative approach with in-depth interviews, observation, and documentation as data techniques. The results of this study indicate that the construction of the preachers and preachers about the urgency of the religious pulpit as a basis for prevention and corruption in Malang Raya has a strong potential as well as cultural capital to inject the consciousness of the mustami 'or audiences who are mostly officials, although there are variants of construction between the preachers and the muballigh at the Masjid Government of Malang Raya, including theological construction, tasawuf construction, jinnayah fiqh construction, eschatological construction, and qawaidul fiqihiyah construction. Meanwhile, the role of prevention and resistance to corruption in the Baiturrohim mosque in the City Hall of Malang through the religious pulpit has been carried out even though studies on the theme of corruption are not specifically discussed, but are tucked into various themes of sermons and lectures. The beginning of what happened at the Baiturrahman Grand Mosque in Malang Regency and the An Nuur Mosque in Batu City, some of the momentum of the religious pulpit which was used as the basis for preventing and eradicating corruption was expressed in religious activities such as religious activities, weekly and monthly recitations, Friday sermons, and instructions. commemoration of Islamic holidays. Through the religious pulpit, the preachers and preachers play a significant role as spiritual generators capable of bringing about social change by expressing Allah's Jalali nature from His masculinity, such as the nature of Al-Mudzil which means Allah is the Most Humiliating Essence; Al-Dlar, the Danger-Givering Essence; Al-Qabidu, the Essence of the Most Narrowing; Al-Muntaqimu The Essence of the Most Giving Reply; Syadidul Iqab, the Essence of the Most Severe Torment, and; Syari'ul Hisab, the Essence of the Most Fast, His Audit Power. This effort is carried out as a shock therapy for officials so that they are able to behave honestly and trustfully.